PERAN PALANG MERAH INDONESIA (PMI) DALAM MENINGKATKAN AKSESIBILITAS PELAYANAN PUBLIK DI KANTOR UNIT DONOR DARAH PMI DI KOTA MEDAN - Tobing, Angela Novenita L; Tobing, Artha; Rajagukguk, Jonson (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This study aims to describe and describe the Role of the Indonesian Red Cross (PMI) in Improving Accessibility of Public Services at the PMI Blood Donor Unit Office in Medan City. The type of research used is qualitative research with a descriptive nature, descriptions of interview results and documentation studies so that it is able to describe various things related to the Role of the Indonesian Red Cross (PMI) in Improving Accessibility of Public Services at the PMI Blood Donor Unit Office in Medan City. The data obtained were analyzed qualitatively and described in descriptive form. The results of this study indicate that the supervision carried out by the Indonesian Red Cross (PMI) in improving Accessibility of Public Services at the PMI Blood Donor Unit Office in Medan City has not been effective enough. This is caused by several obstacles for PMI in improving accessibility of public services at the blood donor unit office, usually including limited resources, such as the number of medical personnel, equipment, and budget. In addition, the lack of public awareness of the importance of blood donation as well as logistical constraints and locations that are difficult to reach are also challenges. These factors can hinder PMI's efforts to provide optimal and equitable services to the community.